Promotion Nationale: forty-five years of experience of public works in Morocco - Hind Jalal (Levy Economics Institute of Bard College, 2007)
Created in 1961, Promotion Nationale (PN) is an autonomous public entity in charge of mobilizing an underemployed or unemployed workforce for the implementation of labor-intensive projects, calling upon a simple technology likely to provide employment to unskilled workers. It is one of the major programs of social protection in Moroccothe oldest, most important, and best-targeted social program in the country. Vis-à-vis the importance of rural underemployment, especially during dry years, estimated per million working days, PN aims to improve employment opportunities by developing collective working methods, and by generating large-scale investment for the realization of public infrastructure projects and rural equipment. This institution aims at limiting rural migration through the permanent improvement of local incomes and living conditions. It thus constitutes a safety net for a large part of the population, especially in rural areas. Forty-five years after its creation, PN has at its credit an important and single assessment regarding the fight against unemployment with minimal management costs, in spite of certain difficulties and limitations that hinder the organization, particularly in terms of the geographical targeting of rural poverty zones.
Keywords: J18; J23; O1; O15; 330; Public Works; Employer of Last Resort; Country Experiences